Studies on achievement at the University of the Philippines - Elequin, Eleanor (Education quarterly.)
This study is designed to test the hypotheses and incidentally to learn whether oral or written English is more adequately comprehended. The studies are a beginning toward understanding the complex phenomenon of student achievement. Six classes of junior standing were available for experimental purposes during the second semester of the year 1959-1960. The study reported superior comprehension among a sample of 82 students of junior standing in the Graduate College of Education of the University of the Philippines for written material as compared with oral material.